Salesperson Deviant Behavior in Indonesian Restaurant Service Attendants - Nugroho, Agustinus; Oktavio, Adrie; Kartika, Endo Wijaya (International Review of Management and Marketing, 2019)
Workplace deviance has emerged into a well-researched construct within these past 10 years. The purpose of this study is to explain the relationship between abusive supervision and salesperson deviant behavior, moderated by negative reciprocity beliefs (NRB). The respondents were 150 full time service attendants, in the sense that their job description includes dealing with customers and selling menu to the customers. This produces a certain deviant behavior related to the customers. The data was processed using Hierarchical Moderated Regression Analysis (HRMA) using SPSS 23. We found that abusive supervision has direct relationship to salesperson deviance, both positively and significantly. NRB is also revealed to have a moderating effect in the relationship between abusive supervision and salesperson deviance, in which the relationship is stronger when the salesperson endorses negative reciprocity beliefs rather than not. In conclusion, restaurants may have to pay serious attention to working condition. Not only abusive supervision will affect the restaurant working condition, but also the service perceived by the customers which in the end will lead to financial problems. These service attendants may project their deviant behavior stronger after receiving abusive treatment, when they endorse negative reciprocity beliefs. Keywords: abusive supervision; negative reciprocity beliefs; salesperson deviance; restaurant service attendants JEL Classifications: D23, J24, J53 DOI: https://doi.org/10.32479/irmm.8138